Development of Hospital Formulary as a Patient Safety Drug Delivery System in Promoting Rational use of Drugs in Tertiary Care Hospital - Tahniyath, Fatima; Hafeez, Fatima; Sultana, Hasbeen; Ashfaq Hussain, Mohammed; Azeez Basha, Syed Abdul (Indian Journal of Pharmacy Practice)
Objective: To constitute a Pharmacy Therapeutic Committee (PTC) and compile, design, develop and publish Owaisi Hospital and Research Centre (OHRC) Hospital Formulary for a tertiary care multi speciality hospital as a patient safety drug delivery system in promoting rational use of drugs. Methodology: PTC Committee was constituted and a descriptive form was designed for acquisition of data for drugs prescribed in respective departments and information pertaining to treatment modalities. The content of monographs to be incorporated was approved by PTC. The latest drug list was obtained from central pharmacy, respective departments/specialties and nursing stations. Subsequently, drugs were classified therapeutically along with USFDA pregnancy risk category; individual drug monographs were prepared, required ancillary information was added and lastly compared with WHO Essential Drugs List (EDL). Copies of the formulary were given to Medical Superintendent, Chief Medical Officer, and Chief Pharmacist and all the departments of Owaisi Group of Hospitals for implementation in the hospital as a tool to promote rational drug use. Results: PTC approved OHRC Hospital Formularyas a handy desk reference was compiled in 530 pages containing 306 generic drugs and FDCs. About 58 drugs were identified as Category A and B, 138 drugs as Category C, D, B/D, A/C and C/D and 7 drugs as Category X. Conclusion: Hospital formulary reflects the current clinical judgment of medical staff ensuring rational drug therapy, controlling drug costs, evidence based prescribing to reduce variation in the levels of treatment; additionally it helps in better inventory control by avoiding zero stock level and to limit the number of brands for each generic drug..
Keywords: FDC-Fixed dose composition; Hospital Formulary; Inventory control; Monograph; Tertiary care; Rational drug use